Faktor Penyebab Perceraian dan Implikasinya dalam Pelayanan Bimbingan dan Konseling - Mega Novita Sari; Yusri Yusri; Indah Sukmawati (Jurnal Konseling dan Pendidikan, 2015)
Marriage is the desire of most human beings in the world. Two different beings and different backgrounds united by God to be complementary. Marriage aims to foster harmonious family, happy based belief in one God. But reality shows that not all who have made a marriage is always followed by a harmony in their relationships, even some who ultimately failed in his marriage. Marriage should be maintained integrity  no longer considered causing disharmony in the household that cause conflict in the family that can result in divorce in the family. The purpose of this study was to determine the cause of divorce in the Religious Padang.The method used in this research is descriptive quantitative method. Subjects were individuals who filed a divorce case in Padang Religious Court, amounting to 80 people. Means of data collection using questionnaires. Data were analyzed using percentage formula.Results of the study revealed that internal factors cause people divorced in Padang High Religious Court that the attitude aspects of egocentrism in the family as much as 65.26% and in the interpretation of the behavioral aspects of rage as much as 56.46%. External factors cause people divorced in Padang High Religious Court that the negative aspects of the association made the couple as much as 62.51%.From the research, advice that can be given to the counselor that should be able to provide help in minimizing cases of divorce by providing counseling services such as information services, content mastery services, individual counseling and mediation services that can help the problems experienced by individuals who are getting a divorce so it is not the occurrence of divorce.